2019
DOI: 10.1038/s12276-019-0293-4
|View full text |Cite
|
Sign up to set email alerts
|

A protective mechanism of probiotic Lactobacillus against hepatic steatosis via reducing host intestinal fatty acid absorption

Abstract: The gut microbiome has been known to contribute up to ~30% of the energy absorption of the host. Although various beneficial mechanisms of probiotics have been suggested for non-alcoholic fatty liver disease (NAFLD), whether and which probiotics impact the host’s intestinal energy absorption have not yet been quantitatively studied. Here, we suggest a novel mechanism of probiotics against NAFLD, in which Lactobacillus rhamnosus GG, the most common probiotic, shares intestinal fatty acids and prevents the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 69 publications
4
52
1
2
Order By: Relevance
“…Chronic oral administration of Lactobacillus reduced weight gain, body fat mass, and hepatic lipid accumulation during high-fat diet feeding, without altering dietary calorie intake or fecal calorie excretion [71]. Pyrosequencing data show that the ratio of Firmicutes to Bacteroidetes is unchanged by LGG treatment, despite the dramatic changes in metabolic phenotypes [71]. Another study also suggests a similar result and shows that Lactobacillus strains reduce intestinal free fatty acids, resulting in a loss of body weight [72].…”
Section: Host and Microbiota Competition In Dietary Energy Harvestmentioning
confidence: 89%
See 2 more Smart Citations
“…Chronic oral administration of Lactobacillus reduced weight gain, body fat mass, and hepatic lipid accumulation during high-fat diet feeding, without altering dietary calorie intake or fecal calorie excretion [71]. Pyrosequencing data show that the ratio of Firmicutes to Bacteroidetes is unchanged by LGG treatment, despite the dramatic changes in metabolic phenotypes [71]. Another study also suggests a similar result and shows that Lactobacillus strains reduce intestinal free fatty acids, resulting in a loss of body weight [72].…”
Section: Host and Microbiota Competition In Dietary Energy Harvestmentioning
confidence: 89%
“…Furthermore, the increase of these specific gut bacteria, which consume dietary substrates results in a decrease in the remaining nutrients in which, in turn, can reduce the amount of nutrients that can be absorbed by the host. Lactobacillus bacteria consume fatty acids during cultivation and delay the intestinal absorption of oleic acids in high-fat diet-fed mice [71]. Chronic oral administration of Lactobacillus reduced weight gain, body fat mass, and hepatic lipid accumulation during high-fat diet feeding, without altering dietary calorie intake or fecal calorie excretion [71].…”
Section: Host and Microbiota Competition In Dietary Energy Harvestmentioning
confidence: 99%
See 1 more Smart Citation
“…Plentiful studies have shown the extensive salubrious effects of probiotics (e.g., Lactobacillus and Bifidobacterium) on liver disease. As shown in high-fructose or high-fat diet-induced experimental NAFLD models, Lactobacillus rhamnosus GG ameliorated NAFLD by (1) control of gut microbiome; (2) repair of intestinal barrier; and (3) suppression of hepatic steatosis, inflammation, and lipid accumulation [83,84]. Bifidobacterium serves to protect against secretion of pro-inflammatory cytokines and dysfunction in intestinal barrier both in vitro and in vivo [85].…”
Section: Probioticsmentioning
confidence: 96%
“…Recent studies suggest that probiotic administration may impact the lipid profile by affecting their absorption or metabolism [76][77][78]. With this in mind, we also quantified the plasmatic FA profile of the dams and pups.…”
Section: Discussionmentioning
confidence: 99%